2014
DOI: 10.1097/igc.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden and Outcomes of Patients With Platinum Resistant/Refractory Recurrent Ovarian Cancer: A Reality Check

Abstract: Patients had a complex array of symptoms and significant symptom burden, which was commonly the reason for treatment. Although chemotherapy improved symptoms in about half of the patients, many did not benefit and progressed rapidly. Our findings support research into the use of patient reported outcome measures to document symptoms, adverse events, and subjective benefit, both in clinical trials and in clinical practice, in this patient population. Our findings highlight the need to develop prognostic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…3 The key points for this article are (1) patients with platinum resistant/refractory recurrent ovarian cancer self-completed an HRQoL booklet before starting palliative chemotherapy (baseline) and (2) a subset of patients completed a structured interview.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 The key points for this article are (1) patients with platinum resistant/refractory recurrent ovarian cancer self-completed an HRQoL booklet before starting palliative chemotherapy (baseline) and (2) a subset of patients completed a structured interview.…”
Section: Methodsmentioning
confidence: 99%
“…14 This article uses baseline data from SRQ, QLQ-C30/OV28, and FACT-O/FOSI; data from the other time points and questionnaires are reported separately. 3,15 Optimality Criteria…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Although chemotherapy has been shown to improve symptoms in most platinum-sensitive patients, approximately half of platinum-resistant patients do not benefit. 4 It is shown that approximately 30% of patients previously treated with chemotherapy and/or surgery report disturbed sleep, fatigue, or numbness/tingling of moderate severity, whereas approximately 20% report back pain, feeling bloated, or constipation of at least moderate severity. 5 Moreover, cancer-related symptoms vary by cancer type, type of treatment, sex, and age and are reported to be associated with psychological distress and reduced quality of life.…”
mentioning
confidence: 99%